2005
DOI: 10.1021/ol0507266
|View full text |Cite
|
Sign up to set email alerts
|

Unique Diketopiperazine Dimers from the Insect Pathogenic Fungus Verticillium hemipterigenum BCC 1449

Abstract: [structure: see text]. Vertihemiptellides A (1) and B (2), unique diketopiperazine dimers, were isolated from the insect pathogenic fungus Verticillium hemipterigenum BCC 1449. Structures of these compounds were elucidated by NMR and mass spectral analysis, and the stereochemistry of 1 was determined by X-ray crystallography. The absolute stereochemistry of bisdethiodi(methylthio)-1-demethylhyalodendrin (3), previously isolated from the same fungus, was revised to the (3R,6R) configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 13 publications
1
41
0
Order By: Relevance
“…The presence of the diketopiperazine 127 as a co-metabolite in BCC 1449 indicated that replacement of the a-H-atoms with S-atoms (i.e., 127 to 128) should take place with retention of configuration. Also other possible mechanisms for the formation of 126 have been considered, for example, a) a radical pathway, instead of the ionic dimerization shown, and b) dimerization of bis-thioradical intermediates, generated by the cleavage of SÀS bond in 128 or directly from 127 [96]. Notoamide E (129) was a key precursor in the biosynthesis of prenylated indole alkaloids in a marine-derived fungus Aspergillus sp., which was produced by the fungus in the early phase of growth and was presumably rapidly converted to notoamide E4 (130) [97].…”
mentioning
confidence: 99%
“…The presence of the diketopiperazine 127 as a co-metabolite in BCC 1449 indicated that replacement of the a-H-atoms with S-atoms (i.e., 127 to 128) should take place with retention of configuration. Also other possible mechanisms for the formation of 126 have been considered, for example, a) a radical pathway, instead of the ionic dimerization shown, and b) dimerization of bis-thioradical intermediates, generated by the cleavage of SÀS bond in 128 or directly from 127 [96]. Notoamide E (129) was a key precursor in the biosynthesis of prenylated indole alkaloids in a marine-derived fungus Aspergillus sp., which was produced by the fungus in the early phase of growth and was presumably rapidly converted to notoamide E4 (130) [97].…”
mentioning
confidence: 99%
“…This observation was supported by the fact that the aliphatic CH 2 and CH groups at d(C) 29.4 (C(8)) and 54.5 (C(9)) in 4 were replaced by the olefinic CH group and the quaternary C-atom at d(C) 112.2 (C(8)) and 124.4 (C(9)) in 2, respectively. The placement of the C¼C bond at C(8) and C(9) was further 3 ). From the above deductions, the structure of 2 was assigned to be (6S)-3-{[2-(1,1-dimethylprop-2-en-1-yl)-5,7-bis(3-methylbut-2-en-1-yl)-1H-indol-3-yl]methylidene}-6-methylpiperazine-2,5-dione, which was named dehydroechinulin.…”
mentioning
confidence: 99%
“…Vertihemiptellides A (281) and B (282), unique diketopiperazine dimers, were isolated from the insect pathogenic fungus Verticillium hemipterigenum [204]. Both compounds exhibited growth inhibitory activity against Mycobacterium tuberculosis but also showed moderate cytotoxic activities, see Table 8.…”
Section: Epipolythiodioxopiperazinesmentioning
confidence: 99%
“…The epicorazines A(203), B(204), C(205), and 3822-A(206) were isolated from fermentations of Stereum hirsutum[158] and from the saprophyte Epicoccum nigrum (epicorazine A and B), E. purpurascens (epicorazine B)…”
mentioning
confidence: 99%